2001
DOI: 10.1063/1.1339991
|View full text |Cite
|
Sign up to set email alerts
|

Interdiffusion of In and Ga in InGaN/GaN multiple quantum wells

Abstract: Thermal stability of InxGa1-xN/GaN multiple quantum wells with InN mole fraction of ∼0.23 and ∼0.30 was investigated by postgrowth thermal annealing. Low temperature photoluminescence spectroscopy was employed to determine the temperature dependence of the interdiffusion coefficient of In and Ga in InGaN/GaN quantum wells. The interdiffusion process is characterized by a single activation energy of about 3.4±0.5 eV and governed by vacancy-controlled second-nearest-neighbor hopping. Due to composition inhomogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
60
1

Year Published

2002
2002
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(62 citation statements)
references
References 16 publications
1
60
1
Order By: Relevance
“…This is because bulk diffusion is negligible at typical growth temperatures, having much too high an energy barrier, such as ~3.4 eV for interdiffusion of In and Ga in InGaN 19 . However, the barriers are greatly reduced at surfaces.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This is because bulk diffusion is negligible at typical growth temperatures, having much too high an energy barrier, such as ~3.4 eV for interdiffusion of In and Ga in InGaN 19 . However, the barriers are greatly reduced at surfaces.…”
Section: Resultsmentioning
confidence: 99%
“…If thermodynamic equilibrium were achieved throughout the NW, no core-shell structure would be observed. In reality, however, the alloy CPs in NWs are expected to be distinctly different from the equilibrium distribution, because bulk diffusion with an energy barrier of a few eVs 19 is negligible at typical growth temperatures. On the other hand, local equilibrium is often established in the near surface region due to the more rapid surface (and sub-surface) diffusion with a much smaller energy barrier in the order of 1 eV 20 or smaller.…”
Section: Introductionmentioning
confidence: 99%
“…From MEIS measurement, 10 we found that there exists a low-indium region near the bottom InGaN/ GaN interface. Since the atomic bond strength of GaN is quite larger than that of InN, 22,23 the thermal stability of the In-rich InGaN QW layer was improved when the region near the bottom interface became compositionally graded to the low-indium content InGaN layer with stronger bond, resulting in 1-nm-thick InGaN layer on GaN even after 10 s GI. 24 By increasing GI time from 0 to 10 s in four periods of MQW, structural properties of In-rich InGaN and LT-capped GaN layers were significantly improved and the integrated PL intensity increased, while the full width at half maximum ͑FWHM͒ decreased to 40 meV at 12 K. The PL peak showed a blueshift from 420 to 380 nm by increasing GI time, and more details on optical properties of the MQW can be found in Ref.…”
Section: B Decomposition and Mass Transport Processes During Gi In Imentioning
confidence: 99%
“…The fact that we also observe a reduction of the In-content of the layers itself from x ¼ 0.33 to x ¼ 0.2 may be an evidence for an additional diffusion of In-atoms into the GaN barrier layers. The In-diffusion coefficient in c-InGaN is not known, however, the coefficient of In-diffusion in hexagonal material has been measured to be about 1 Â 10 --19 cm 2 s at 900 C with an activation energy of 3.4 eV [10]. Extrapolating the In-diffusion coefficient to the c-InGaN growth temperature of 600 C, we obtain a diffusion length of In during growth below 0.01 nm.…”
mentioning
confidence: 98%